Diarrhoeal Diseases in the Slums of Khulna City: Prevalence and Cost Analysis (Journal of Asian Development Studies, 2013)
This study estimates the prevalence and cost of diarrhoeal among the slum dwellers of Khulna city in Bangladesh. Estimation of health production function and Logit model gave useful insight about the factors influencing the health of slum people and the probability of the people being affected by diarrhoeal. It exposed that the children under five years old and the house wives are more vulnerable to this diarrheal diseases. However the people who have substantial year of schooling are less vulnerable to this disease. Each episode of diarrhoeal costs huge for those low income families. Average suffering days are 4 and it costs BDT 445 per day in each episode which is more than their per day income. Sharing of toilet and water sources implies significant positive relation with diarrhoeal prevalence. Consciousness and development in behavioral attitude can reduce the risk of diarrhoeal diseases.